Tinjauan Kondisi Fisik Pemain Bola Voli Putri Ekstra Kurikuler SMAN 4 Kerinci - Alifa, Ogilvia; Putra, Roki; Hidayat, Muhammad (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
This research aims to understand the physical condition of female volleyball players in the extracurricular club at SMAN 4 Kerinci. The type of research is descriptive quantitative, the population consists of 16 students who participate in the extracurricular club. The sample is determined using total sampling technique, i.e., taking the entire population as a sample. Data is analyzed using descriptive techniques and subsequently presented in the form of tables and diagrams. The results of the research indicate that the level of physical condition of the female volleyball players in SMA Negeri 4 Kerinci can be specifically concluded from several components that most affect the result of the physical condition level itself, namely the push-up strength test very good there is 1 person (6%), good there are 6 people (38%), category sufficient there are 3 people (19%), category less good there are 5 people (31%), and one person belongs to the category very less good (6%). The results of the speed test are very good there are 2 people (13%), good there are 8 people (50%), category sufficient there are 5 people (31%), category less good there is 1 person (6%), and no one belongs to the category very less good (0%) and the results of the Squat Thrus test are very good there are 4 people (25%), good there are 5 people (31%), category sufficient there are 4 people (25%), category less good there are 3 people (19%), and no one belongs to the category very less good (0%). Based on the average value which is 45.4375, which means the level of physical condition of the female volleyball players in SMA Negeri 4 Kerinci is in the good category.